Penerapan Etika Komunikasi dalam Kegiatan Table Manner sebagai Upaya Meningkatkan Keterampilan Mahasiswa - Muria Putriana; Wina Puspita Sari; Adi Budi Satrio; Qoryna Noer Seyma El Farabi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The application of communication ethics in table manner activities is a form of etiquette learning related to how a person behaves and interacts politely at the dinner table. Table manner activities not only teach skills in the use of tableware, but also how to communicate politely, maintain ethics, and show respect for the interlocutor in formal situations. Communication etiquette in table manner includes the right choice of words, good body posture, and how to convey a message without disturbing the comfort of others around you. This study aims to identify the importance of communication ethics in table manner activities, as well as its impact on the formation of a positive self-image and better interpersonal relationships. By applying good communication ethics through table manners, individuals are expected to improve the quality of their social interactions in various formal and informal situations, especially in the field of public relations. The implementation of the manner table at the Horison Hotel Bekasi, West Java and the method was carried out using direct observation, in-depth interviews and documentation. The results and discussions obtained from the table manner participants were 64 people, one of the results was the application of table manner to increase awareness of the importance of ethics in communicating in the professional world. Participants who participated in table manner activities showed a better understanding of manners, both in the use of tableware and in conveying polite and polite communication.